Effect of Moderate-Intensity Continuous Training (MICT) on Pancreatic Islet of Langerhans’ Morphology and Cell Count of Female Rats (Rattus norvegicus) Exposed to High-Calorie Diet - Sari, Eny Wulan; Setiawan, Hayuris Kinandita; Rahniayu, Alphania; Herawati, Lilik (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: Moderate-intensity continuous training exercise did not affect the diameter of pancreatic islets of Langerhans in a high-calorie diet subject. Moderate-intensity continuous training exercise did not affect the number of pancreatic islets of Langerhans in a high-calorie diet subject.   Abstract Introduction: Calorie consumption that exceeds normal limits each year can be a risk factor in causing diabetes mellitus (DM). This condition causes the body to be in a state of hyperglycemia, which will trigger changes in the diameter and number of Langerhans islet cells. Moderate-intensity continuous training (MICT) is recommended as a physical exercise method to help prevent DM. Methods: This true experimental study used a randomized post-test-only control group design. Wistar female rats were randomly divided into three large groups: (A) the control group without a high-calorie diet and exercise, (B) the group with a high-calorie diet without exercise, and (C) the group with both a high-calorie diet and exercise (MICT). This experiment lasted for four weeks with an exercise frequency of five times a week. One-way analysis of variance (ANOVA) revealed that group differences in diameter had results of p=0.130 (p>0.05), while the number of islets of Langerhans had results of p=0.068 (p>0.05). Results: There was no significant difference in the islets of Langerhans’ diameter between the three groups (p=0.116). The number of islets of Langerhans also had no significant differences (p=0.068). Conclusion: There was no significant effect of a high-calorie diet and MICT physical exercise on the diameter and number of pancreatic islets of Langerhans cells in female rats (Rattus norvegicus).